Weed seed predation, agricultural intensity and landscape composition data in winter wheat fields in Skåne, Southern Sweden - Daouti, Eirini Lamprini; Jonsson, Mattias; Feit, Benjamin (Swedish University of Agricultural Sciences, 2022)
Weed seed predation, agricultural intensity and landscape composition data in winter wheat fields in Skåne, Southern Sweden
- Data on weed seed predation were collected by using seed cards.
- Data on weed seed availability were collected by using suction sampling
- Data on management intensity data were collected from an ad-hoc selection of farming professionals
- Data on habitat refugia were extracted through landscape analysis using the program ArcMap(ESRI, v. 10.4.1)
- Data on and carabid community, that were used to estimate the community strength of seed predation, were collected using pitfall traps.

The dataset consists of five files that include data on:

1.Data on weed seed predation were collected by using seed cards. (1.seed_predation.csv)
2.Data on weed seed availability were collected by using suction sampling (2.seed_availability.csv)
3.Data on management intensity data were collected using ad-hoc selection of farming professionals. Specifically, communication with persons working with farm management in different roles (owner, tenant, employed) about management intensity. As we have not documented the role, they cannot be identified (3.management_intensity.csv)
4.Data on habitat refugia were extracted through landscape analysis using the program ArcMap(ESRI, v. 10.4.1) (4.habitat_refugia.csv)
5.Data on and carabid community that were used to estimate the community strength of seed predation were collected using pitfall traps. (5.community_strength_of_seed_predation.csv)

Should be noted that there is no coded key to the fields 1 to 13. The field data are linked with another dataset, where the fields have other field ID numbers and there is no correlation between this numbering and the one used.

Ogräsfröpredation, jordbruksintensitet och landskapssammansättningsdata i höstvetefält i Skåne, Sverige
- Data om predation av ogräsfrö samlades in genom att använda frökort.
- Data om ogräsfrötillgänglighet samlades in med hjälp av sugprovtagning
- Data om förvaltningsintensitetsdata samlades in från ad hoc-urval av jordbrukare
- Data om habitatrefugia extraherades genom landskapsanalys med hjälp av programmet ArcMap(ESRI, v. 10.4.1)
- Data om och karabidgemenskap som användes för att uppskatta gemenskapsstyrkan hos fröpredation samlades in med hjälp av fallgrop.

Datauppsättningen består av fem filer som innehåller data om:

1. Data om predation av ogräsfrö samlades in genom att använda frökort. (1.seed_predation.csv)
2. Data om tillgänglighet av ogräsfrö samlades in med hjälp av sugprovtagning (2.seed_availability.csv)
3. Data om förvaltningsintensitetsdata samlades in med hjälp av ad hoc-val av jordbrukare. Specifikt kommunikation med personer som arbetar med gårdsdrift i olika roller (ägare, arrendator, anställd) om förvaltningsintensitet. Eftersom vi inte har dokumenterat rollen kan de inte identifieras (3.management_intensity.csv)
4. Data om habitatrefugia extraherades genom landskapsanalys med hjälp av programmet ArcMap (ESRI, v. 10.4.1) (4.habitat_refugia.csv)
5. Data om och karabidgemenskap som användes för att uppskatta gemenskapsstyrkan hos fröpredation samlades in med hjälp av fallgropar. (5.community_strength_of_seed_predation.csv)

Det bör noteras att det inte finns någon kodad nyckel till fälten 1 till 13. Fältdata är kopplade till ett annat dataset, där fälten har andra fält-ID-nummer och det inte finns någon korrelation mellan denna numrering och den som används.
Ogräsfröpredation, jordbruksintensitet och landskapssammansättningsdata i höstvetefält i Skåne, Sverige
Keywords: agricultural management; jordbruksförvaltning; habitat; utbredningsområde; pitfall trap; weed seed predation; predation av ogräsfrö; Ecology; Ekologi; Agricultural Science; Jordbruksvetenskap; Boundaries; Administrativa gränser